A Cuticular Hydrocarbon of Blowflies (Chrysomya spp.) from Sarawak: Implication and Application in Forensic Entomology - Rizoh, Bin Bosorang (unimas, 2017)
The variation occurred in cuticular hydrocarbon (CHC) profile may hinder its potential as an alternative character for species identification, and may affect the application of this technique in taxonomy. Since differences in CHC composition was detected at insects’ development stages, there is a possibility that this variation could be used to estimate insect age based on its cuticular hydrocarbon profile. Thus, this study aim to investigate the potential of CHC composition as an alternative character for species identification and for age determination. This study was conducted mainly on forensically important blowfly Chrysomya megacephala as this species is one of the most significant group for post mortem interval (PMI) estimation during the first two weeks of decomposition and the most prevalent calliphorid species recovered from corpses or animal carcasses in Malaysia. This thesis present work examining the distribution and variation of CHC composition of forensically important blowfly C. megacephala between localities, generations and developmental stages with two main objectives.